Granulomatous and xanthogranulomatous prostatitis: A case report - Al-Naimi A (17191300) (2022)
Granulomatous prostatitis is a rare condition that is diagnosed only by histopathological examination. Though rare, the condition was reported to have different presentations (mimicking prostate cancer or prostatitis and prostatic abscess) and to have different etiologies which classified it into three main entities; nonspecific (idiopathic), post-surgery, and specific. Specific granulomatous prostatitis is further sub-classified to infective, xanthogranulomatous, Malacoplakia and associated with systemic granulomatous disease and allergy. We hereby report a rare case of xanthogranulomatous prostatitis that presented with persistent urinary tract infection. Other Information Published in: Urology Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eucr.2021.101887